Sustaining user engagement with behavior-change tools - Karapanos, Evangelos (My University, 2015)
Technologies for behavior change have immense potential. Consider, for instance, the case of physical activity trackers. The healthcare systems are facing unprecedented challenges. Western lifestyles, now spreading throughout the world, have had a direct impact on the increase of chronic diseases, which today account for nearly 40 percent of mortality cases. Despite significant recent advances, one could argue that research and practice in behavior-change technologies are still in their infancy. The industry is currently following a technology push paradigm, appealing to the user's interest in experimenting with self-quantification. Ensuring engagement over the long term is not just a question for research; it is highly relevant for industry as well. While the current market is largely dominated by the aesthetics of wearable devices and their user interfaces, and not many structural differences exist among the products from a behavior-change perspective, it is very likely that with the increasing saturation of the market, companies will be required to prove the effectiveness of their products in supporting behavior change.
Keywords: Behavior change; User interfaces; Health-care system; Physical activity; Structural differences; User engagement; User's interest; Wearable devices